(untitled) (Revista Argentina de Cirugía, 2026)
Background:The risk factors (RF) for difficult laparoscopic cholecystectomy (DLC) have been identified in many observational studies. Objective: The aim of this study is to identify the preoperative RF for DLC in a secondary care public hospital. Material and methods: We conducted a prospective cross-sectional cohort study of patients > 18 years undergoing laparoscopic cholecystectomy between January and December 2019. The following variables were analyzed: age, sex, body mass index (BMI), cholelithiasis, acute pancreatitis, acute or chronic cholecystitis, Mirizzi syndrome, ERCP within the previous month, episodes of biliary colic in the last month, presence of at least one colic within one week before surgery, white blood cell count, liver enzymes, total bilirubin, preoperative ultrasound and history of upper abdomen surgery. Results: The rate of DLC was 47.5%. Conversion rate to conventional surgery was 11.25% and 100% were categorized as DLC. The RF for DLC included male sex (OR, 4.50; 95% CI,1.60-12.62; p = 0.004), colic within 1 week before surgery (OR, 7.17; 95% CI,1.89-27.23; p = 0.004), gallbladder wall thickening (OR, 4.90; 95% CI,1.90-12.70; p = 0.001), edema around the gallbladder (OR, 7.14; 95% CI, 1.45-35.13; p = 0.016), hidrops gallbladder (OR, 4.94; 95% CI,1.44-16.88; p = 0.011) and previous surgeries (OR, 4.38; 95% CI, 1.27-15.10; p = 0.001). On multivariate analysis, male sex and previous surgery were associated with higher risk of DLC (OR, 6.63; 95% CI,1.75-25.08; p = 0.005; and OR, 11.70, 95% CI,1.48- 92.37; p = 0.020, respectively).